Mechanisms of rhizosphere plant-microbe interactions: molecular insights into microbial colonization - Yang, Luna; Qian, Xin; Zhao, Zeyu; Wang, Yaoyao; Ding, Gang; Xing, Xiaoke (Frontiers in Plant Science, 2024)
The rhizosphere, as the "frontline" of plant life, connects plant roots, rhizosphere microorganisms, and surrounding soil, plays a crucial role in plant growth and health, particularly in sustainable agriculture. Despite the well-established contribution of plant-microbe interactions to plant health, the specific molecular mechanisms remain insufficiently understood. This review aims to summarize the physiological adjustments and signal modulation that both plants and microorganisms undergo within this unique ecological niche to ensure successful colonization. By analyzing key processes such as chemotaxis, root attachment, immune evasion, and biofilm formation, we uncover how plants precisely modulate root exudates to either recruit or repel specific microorganisms, thereby shaping their colonization patterns. These findings provide new insights into the complexity of plant-microbe interactions and suggest potential directions for future research in sustainable agriculture.